DEPRESSION RELATIONSHIP WITH BLOOD PRESSURE IN THE ELDERLY AT THE TRESNA WERDHA KHUSNUL KHOTIMAH SOCIAL HOME PEKANBARU IN 2018 - Anggrainy, Vivi; Ainiyah, Fakhirah Fitri; Putri, Nidya Triana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Depression is a common mental disorder characterized by constant sadness and loss of interest in activities that are usually liked, accompanied by an inability to carry out daily activities. The Elderly group experiences depression due to physical changes and environmental social conditions. Other risk factors that can cause depression in the elderly include biological factors, marital status, and psychosocial factors. Biological and psychosocial factors have a relationship with changes in the levels of hormones and neurotransmitters in the body. Changes in hormone levels and neurotransmitters can cause changes in blood pressure. Blood pressure is normal if the systolic blood pressure is less than 120 mmHg and the diastolic blood pressure is less than 80 mmHg and high blood pressure if the systolic blood pressure is more than 140 mmHg and the diastolic blood pressure is more than 90 mmHg. Objective: To determine the relationship of depression to blood pressure in the elderly at the Tresna Werdha Social Home Khusnul Khotimah Pekanbaru in 2018. Research Methods: The method used in this study is analytic observation with a cross-sectional design. The sampling technique used the total sampling method, where in this study, the population was a sample, but after the exclusion, the number of samples obtained was 41 respondents. Data collection was carried out by observations made by interviewing respondents using questionnaires and blood pressure measurements using a Sphygmomanometer and stethoscope. Results: Obtained p values (Sig.) Systolic blood pressure and diastolic blood pressure showed several 0.021 and 0.019. This p (Sig.) The value is small of 0.05, and this indicates a significant relationship of depression to blood pressure in the elderly at the Tresna Werdha Khusnul Social Home Khotimah Pekanbaru in 2018. Conclusion: There is a significant relationship between blood pressure depression in the elderly at PSTW Khusnul Khotimah Pekanbaru in 2018.